Naftopidil molecular salts with improved dissolution and permeation - Mannava, M. K. Chaitanya; Dandela, Rambabu; Tothadi, Srinu; Solomon, K. Anand; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Naftopidil (NFPD) is a alpha 1 adrenoceptor antagonist drug. Low solubility and low permeability are the major drawbacks of this drug. The synthesis of multicomponent crystalline forms of this amine functional group drug with carboxylic acid coformers, both achiral and chiral acids, provides a solution to improve its solubility as well as permeability. Nine molecular salts were crystallized by liquid-assisted grinding followed by isothermal crystallization. Single-crystal X-ray diffraction analysis of the molecular salts showed that the structures are stabilized by strong N-H center dot center dot center dot O and O-H center dot center dot center dot O and weak C-H center dot center dot center dot O hydrogen bonds in the solid state. The bulk phase purity of new solid forms was confirmed by powder X-ray diffraction (PXRD), and the crystalline products were further characterized by IR spectroscopy and thermal analytical techniques (differential scanning calorimetry). The molecular salts exhibit superior dissolution rates compared to pure NFPD. However, during dissolution, NFPD showed decrease in concentration after 60 min for all salts due to precipitation. The supersaturation occurred due to salt disproportionation, which generates insoluble NFPD, as confirmed by PXRD of the residue. The salts reach high saturation concentration before 60 min, which is indicative of immediate release formulation to achieve fast onset of therapeutic activity. Moreover, the salts exhibit high saturation in phosphate buffer saline media and improved permeability compared to the pure drug. Finally, the D,L-malic acid racemate of NFPD shows enhanced dissolution and permeability compared to all other salts and pure NFPD.